Energy harvesting from ambient electromagnetic wave using human body as antenna. Issue 2 (1st January 2013) - Hwang, J.H.; Hyoung, C.H.; Park, K.H.; Kim, Y.T.
Abstract : The feasibility of energy harvesting using the human body, which is used instead of a general antenna as an antenna in a low‐frequency band to harvest energy included in an ambient electromagnetic wave, is investigated. Using the presented method, it is possible to harvest much more power in comparison with that possible with the previous method, in which a general antenna is used to harvest power in the high‐frequency band. Also, this method can be easily applied to mobile devices because no antenna is required.